Analysis of the reasons for the grade level preferences of prospective elementary school teachers - salmawati adam (Program Studi Pendidikan Guru Madrasah Ibtidaiyah Institut Agama Islam Negeri Sorong, 2024)
This study aims to understand the reasons for the preference of prospective teachers in choosing the preferred grade level of teaching in elementary schools. This decision-making process is a complex process and is influenced by several internal and external factors that affect the decision of prospective teachers on the selection of teaching classes in elementary schools. Prospective teachers are required to have various competencies, namely pedagogic, social, professional and personality competencies, all of which are an interrelated and mutually supportive unit. It is important for aspiring teachers to understand their own preferences, consider the needs of students at a certain level, and have an appropriate teaching style, making informed decisions. This study uses a qualitative method by collecting data through direct interviews with a sample of 20 respondents of semester VI students, from the Madrasah Ibtidaiyah Teacher Education study program at the Faculty of Tarbiyah, Universit. The results of the analysis showed that there was a balance in each reason of preference for the grade level that prospective teachers wanted to teach, where each had advantages and disadvantages in each specific selected grade level. This highlights that the decision to choose the preferred grade level of teaching prospective teachers in elementary schools is influenced by individual preferences, interests, motivation, experiences during education, and family and social environments.